Three new species of genus Drabescus (Hemiptera: Cicadellidae: Deltocephalinae: Drabescini) from Malaysia - Zou, Hongfen; Lu, Lin; Zhang, Yalin; Cao, Yanghui (Zootaxa, 2026)
Three new species of the leafhopper genus Drabescus Stål, D. digitolamellatus, D. dilatoconnexus and D. medidigitatus spp. nov., are described and illustrated from Malaysia. Detailed morphological descriptions, illustrations, and the sequences of the mitochondrial gene cytochrome c oxidase subunit I (COI) are provided for these three new species.